A methodological checklist for studies of pleasure and enjoyment responses to high-intensity interval training: Part I. participants and measures - Ekkekakis, P.; Hartman, M. E.; Ladwig, A. M. (Journal of Sport & Exercise Psychology, 2023)
For decades, the exercise psychology research literature echoed the conclusion that exercise makes most people feel better, with no clear evidence that this "feel-better effect" is moderated by intensity. An overhaul of the methodological approach subsequently showed that high-intensity exercise is experienced as unpleasant, and the "feel-better effect," although possible, is conditional and therefore not as robust or prevalent as initially thought. Recently, several studies investigating high-intensity interval training (HIIT) have concluded that HIIT is pleasant and enjoyable, despite the high intensity. Considering that HIIT is emerging as an option in physical activity recommendations and exercise prescription guidelines, in part due to these claims, a methodological checklist is presented to aid researchers, peer reviewers, editors, and other readers in critically appraising studies examining the effects of HIIT on affect and enjoyment. This first part addresses the characteristics and number of participants, as well as the selection of measures of affect and enjoyment.